A study of the joint integration between the outputs of higher education and economic growth in Syria - نجار كمال; طالب أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to use the method of joint integration between the outputs of higher education and economic growth in Syria through the application of ARDL models, and is there a long-term equilibrium relationship between these indicators? The most important results of the study were: There is a short-term and long-term relationship for graduates of public universities and graduates of technical institutes on economic growth, while there is no long-term relationship between graduates of postgraduate studies and graduates of higher institutes on economic growth, as there is a short-term relationship between these variables, and based on the error correction model Indicators of higher education graduates explain 0.42% of the changes in economic growth in the long run.